Designing a Website-Based Information System for Cibadak Village Using the Waterfall Method - Setiawan, Ayub; Yulisa Geni, Bias; Laple Satria Putra, Rani (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
This research aims to design an information system based on a website for the village of Cibadak, using the Waterfall methodology. The website-based information system is envisioned to enhance communication and accessibility of vital village-related information for residents and stakeholders. The Waterfall methodology provides a structured approach to the development process, encompassing sequential phases from requirements gathering, design, implementation, testing, and maintenance. By employing this methodology, the study seeks to ensure systematic and comprehensive development, addressing the specific needs and challenges faced by the village of Cibadak. The outcome of this research is expected to offer insights into the effective application of the Waterfall methodology in developing information systems tailored to the requirements of rural communities, thus contributing to improved governance and service delivery at the village level.